Issues and Challenges on the Mental Health Services of a Selected Municipality in Metro Manila: A Case Study - Billote, William Jo Se; Ponce, Ryan (JPAIR Multidisciplinary Research, 2020)
Mental health problem is one of the leading causes of disability worldwide. It makes up one-third of the world population. With the increasing number of individuals with mental health problems and difficulties worldwide, countries such as the Philippines are still in the process of addressing the issue of providing quality mental health care services. This study aimed to identify and evaluate the existing mental health services offered in a selected Municipality in Metro Manila, Philippines. Moreover, this sought to increase knowledge and awareness about mental health services to help solve the issues and challenges identified in this study. The study employed an initial semi-structured interview that can lead to a case study, which is a qualitative research design. The study was conducted in one of the City Health Offices in Metro Manila. Insufficient budget, lack of trained professionals and mental health workers, lack of mental health system framework, not fully implemented mental health law and lack of collaboration and integration were the problems identified in providing quality mental health services. Although the Philippine government exerts effort on filling the gaps in providing treatment and care to those individuals with mental health difficulties, access to mental health institutions in the Philippines favors those near the National Capital Region.